O trabalho escravo contemporâneo: - Rego, Benedita dos Santos (Universidade Federal do Tocantins, 2023)
This study gets to objective to analyse the reports of the Pastoral Land Commission (CPT) about slave labor in Tocantins in 2002 at 2010. In this, seek to definition of the slave labor and your many forms slavery in Brazil. The objective of this search is to know the identified cases of slave labor in north of Tocantins and what actions taken to curb and eradicate this social issues and know many fields of activity explored by workers during the slave labor. To get lager knowledge of issues as actions taken by responsible public bodies of fighting this form of work that continue up to the present. The used methodology constituted through of reading, analyse of documentaries and discussions linked to subject. This study approaches elements that describes the slavery in the reality of surviral of workers. And finally, this study treats legislation referring to slave labor in north of Tocantins and the numbers of rescueds and your public policies to curb and eradicate them.